Reinforced poly(hydroxyurethane) thermosets as high performance adhesives for aluminum substrates. Issue 38 (7th September 2017) - Panchireddy, S.; Thomassin, J.-M.; Grignard, B.; Damblon, C.; Tatton, A.; Jerome, C.; Detrembleur, C.
Abstract : High performance adhesives for bare aluminum are prepared by reinforcing poly(hydroxyurethane) (PHU) thermosets with (functional) nanofillers and poly(dimethylsiloxane). Abstract : Poly(hydroxyurethane) (PHU) thermosets reinforced with (functional) nanofillers were developed to design high performance adhesives for bare aluminum. Solvent-free cyclic carbonate/amine/PDMS formulations loaded with native, epoxy- or cyclic carbonate-functionalized ZnO nanofillers were premixed before deposition and thermal curing onto Al. The results highlight that the addition of PDMS prevents PHUs from delamination of the Al surface by increasing the adhesive hydrophobicity and thus limiting the water uptake. The dispersion of functional fillers within PHUs improves their thermal and mechanical properties. Benchmarking of the adhesive performances of the reinforced PHU glues with existing PHU formulations attests the benefits of dispersing functional fillers and PDMS within a resin and evidences a 270% increase of the shear strength of reinforced PHU adhesives compared to formulations reported in the literature.